Preparation and identification of oxidatin derivaties for Salts and acids of bile for medical uses - Baghdad Science Journal (مجلة بغداد للعلوم)
The purified prepared compounds were identified through different methods of identification i.e, I.R, UV-vi^ble-spectroscopy in addition to (coloured tests) Calculation of the sum of OH groups. TLC techniques were also used to test the purity and the speed ofthe rate of flow (RF).